Securing Property Rights in Transition: Lessons from Implementation of China's Rural Land Contracting Law - Deininger, Klaus (2012)
Motivated by the emphasis on secure property rights as a determinant of economic development in recent literature, we use village- and household-level information from about 800 villages throughout China to explore whether legal reform increased protection of land rights against unauthorized reallocation or expropriation with below-average compensation by the state. In addition to providing nation-wide evidence on a sensitive topic, we find positive impacts, equivalent increasing land values by 30 percent, of reform even in the short term that originated in villages where democratic election of leaders ensured a minimum level of accountability, pointing towards complementarity between good governance and legal reform. Implications for situations where individuals and groups hold overlapping rights to land are explored.